Greener Chemistry for Hybrid Materials, Alcohol‐Free Synthesis with an Epoxy‐Cyclohexyl Precursor. Issue 3 (28th November 2016) - Jiang, Yu; Carboni, Davide; Malfatti, Luca; Innocenzi, Plinio
Abstract : [2‐(3, 4‐Epoxy‐cyclohexyl)‐ethyl]‐trimethoxysilane (ECTMS) is used for designing hybrid organic–inorganic materials through an alcohol‐free sol–gel synthesis. ECTMS sols show a very low reactivity of the epoxide moiety which is accountable for the presence of cyclic species in the dried films. Cyclohexane rings together with cage‐ and ladder‐like structures provide an improved thermal stability to the material up to 300 °C. Abstract : Green synthesis is one of the hot topics in the chemistry of hybrid organic–inorganic materials. A alcohol‐free sol–gel process has been developed to prepare optically transparent hybrid films from an epoxy bearing alkoxide, [2‐(3, 4‐epoxy‐cyclohexyl)‐ethyl]‐trimethoxysilane (ECTMS). The synthesis is simple and effective because only two components, ECTMS and an aqueous solution of NaOH, are employed. Infrared spectroscopy has been used to monitor the reactivity of the precursor sol as a function of the aging time. Organic–inorganic hybrid films have been then prepared with the different sols via spin‐coating. The presence of the cyclohexyl ring slows down dramatically both the epoxide opening and the capability of the resulting diols in forming a tricyclic dioxane derivative. The highly basic conditions employed in the synthesis favor the formation of the cyclohexyl rings and cage‐ and ladder‐like silica structures. The hybrid films have shown a high transmittance in the visible range and a thermal stability up to 200 °C.